Kerentanan Pariwisata dan responnya: Studi Kasus Covid 19 di Kawasan Wisata Kaliurang - Runavia Mulyasari; Gaffari Rahmadian (Gadjah Mada Journal of Tourism Studies, 2022)
This study seeks to understand the impact of the tourism crisis due to the Covid-19 pandemic in the Kaliurang Tourism Area and the emerging vulnerabilities for tourism actors who make tourism their sole livelihood. To understand these conditions, pre-eliminary research was carried out as part of a series of research on tourism and COVID-19. This research was conducted by using qualitative methods from April to October 2021. The results of this pre-eliminary research clearly show that tourism actors in Kaliurang are experiencing a slump due to the COVID-19 pandemic. Tourism, which is the main source of living, is in fact very vulnerable to a prolonged crisis. The impacts and risks that arise in Kaliurang are clearly seen in the economic and socio-cultural sectors. As an effort to survive the tourism actors in Kaliurang are trying to respond to this condition individually and in groups. However, the responses that arise are not only positive but also negative, such as friction and conflict.